1994
DOI: 10.1136/gut.35.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Management of common bile duct stricture caused by chronic pancreatitis with metal mesh self expandable stents.

Abstract: Twenty patients with chronic pancreatitis and signs of biliary obstruction were treated by endoscopic placement of self expandable metal mesh stents, and followed up prospectively. Eleven had been treated previously with plastic endoprostheses. All

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(95 citation statements)
references
References 14 publications
1
90
0
4
Order By: Relevance
“…[7][8][9][10][11] Uncovered metal stents have been placed in refractory BBS patients. [12][13][14] However, their long-term efficacy has been limited owing to their lack of long-term patency. 12,14 Their placement has been associated with epithelial hyperplasia and embedding the stent in the bile duct, thus making their removal extremely difficult.…”
Section: 류충헌 등 양성 담도협착에서 완전 피막형 금속 스텐트 삽입의 효과mentioning
confidence: 99%
“…[7][8][9][10][11] Uncovered metal stents have been placed in refractory BBS patients. [12][13][14] However, their long-term efficacy has been limited owing to their lack of long-term patency. 12,14 Their placement has been associated with epithelial hyperplasia and embedding the stent in the bile duct, thus making their removal extremely difficult.…”
Section: 류충헌 등 양성 담도협착에서 완전 피막형 금속 스텐트 삽입의 효과mentioning
confidence: 99%
“…Deviere et al [85] deployed USEMS in patients (n = 20) with CP, and initially demonstrated relief of cholestasis for up to 33 mo for 18 patients. Repeat ERCP 3 mo later demonstrated that the stent was embedded within the bile duct wall.…”
Section: Pancreatic Pseudocystsmentioning
confidence: 99%
“…In recent years, EUS-guided pseudocyst (EGPD) drainage has gained in popularity since it allow to avoid intervening vessels and target more challenging collections safely when compared to conventional transmural drainage Sauerbruch et al [107] 8 8 8 11 Den Toom et al [108] 8 8 (7 pain relief) 8 17 Sauerbruch et al [109] 24 24 24 24 Delhaye et al [60] 123 88 123 Schneider et al [110] 50 39 48 20 Van der Hul et al [111] 17 17 17 30 Wolf et al [112] 12 9 12 19-22 Schreiber et al [113] 10 7 10 12 Johanns et al [114] 35 23 16 NA Ohara et al [115] Uncovered metal stents have also been evaluated. Since biliary strictures related to CP can be difficult to treat with plastic stents, there have been several studies that examined the use of uncovered self-expanding metal stents (USEMS) in patients with primarily CP [84][85][86][87] .…”
Section: Pancreatic Pseudocystsmentioning
confidence: 99%
“…Because plastic stent are not adapted for a long-term drainage, Deviere et al tested metallic expansive stent with an excellent result in 18/20 patients, after 33 mo of follow-up [64] . Nevertheless, the two remaining patients presented an obstruction of the stent secondary to epithelial hyperplasia in contact with the stent.…”
Section: Endoscopic Treatment Of Biliary Stenosismentioning
confidence: 99%